PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA ANGGARAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI: STUDI KASUS DI BADAN LAYANAN UMUM (BLU) UNIVERSITAS SRIWIJAYA - Ardiansyah a; Isnurhadi h; Marlina Widiyanti (The Manager Review, 2019)
The change of budget approach uses performance-based approach nowadays so that it effect the performance-based accounting and financial reporting system in all government agencies to improve services to public. Contingency theory states that there is no design and use of management control systems that can be applied effectively to all organizational conditions, but particular control system is only effective for a certain situation or organization. This study aimed to examine the effect of budget participation on budget performance with the organizational commitment of as a moderation variable in Sriwijaya University. Data were gathered by means of questionnaire with likert scale. The samples, 113 respondents, obtained using purposive sampling technique, were officials, employees, and lecturers involved in budget planning in Sriwijaya University. This study used instrument test (validity test and reliability test), multiple linear regression test (Y = ?0 + ?1X1 + ?2X2 + ?), hypothesis test (f test and t test), and residual test of moderation variables (Z = a + b1X1 + e ...(1) and | e | = a + b1Y ...(2)) using the IBM SPSS 23. The study result showed that budget participation positively and significantly affected budget performance (R Square value (R2) of about 0.615 and t-test results was significance, 0.000 < 0.05). While organizational commitment did not strenghthen or weaken the relationship between budget participation and budget performance in Sriwijaya University (significant value of about 0.385 > 0.05 (not significant) and the regression coefficient was positive, 0.32).